The impact of Tajweed and Sounds Proficiency on Meditating Quran: An Analytical Study - Hafiz Abdul Quddoos (jihat-ul-islam, 2022)
The Noble Qur'an is a message from Allah Almighty, to this Ummah .Those who read it and meditate on it reach the point of honor and exaltation of the universe that even the angels are covetous of them. In this book, "Mubin" prudence (deep understanding) has been considered the main principle. The most helpful in the deep understanding of the Qur'an is the beautiful pronunciation of the words, (articulation / recital) with which the beauty of the recitation enhances and reaches at the highest level, such that it inspires the listeners to reflect and contemplate . Sometimes the reciter makes such a "WAQF" (pause) that makes it easy to understand the interpretation of the verse .That is why it is ordered to learn the pronunciation of words and places of waqf so one can read as Prophet PBUH taught. Another thing that is helpful in deep understanding is the beautiful voice that matches with Arabic melody, not only it is a treat to ears but also heartwarming, their hearts become soft, tears of divine love and compassion fall from their eyes, it increases faith, firms the belief, fear of Allah prevails over, with the acquisition of divine love and the blessing of righteous deeds and the success of this world and hereafter is obtained. There are also some voices of Jews and Christians who recite in the tone of the transgressors or monks who chant their books to music that is forbidden because these voices harden the hearts and make them prone to temptation.